Design and Evaluation of Enteric Compression-coated Tablet for Chronotherapeutic Drug Delivery - Kanugo, A. Y. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The aim of the present study was to design and evaluate compression-coated pulsatile drug delivery system intended for the treatment of early morning rise in blood pressure. Candesartan cilexetil which is a non-peptide angiotensin II Type 1 receptor antagonist was selected for pulsatile drug delivery. Materials and Methods: Candesartan cilexetil is potent drug and used in the treatment of hypertension and congestive heart failure. Compression-coated tablets were prepared to achieve the predetermined lag time. This coated tablet contains inner core containing active drug, excipients, and outer barrier layers of different compositions of enteric polymers such as Eudragit L 100, S 100, and L100-55 with ethyl cellulose. Both core and coated tablets were evaluated for its flow properties, hardness, friability, weight variations, and dissolution studies. The drug-excipients interactions were carried out by Fourier transform infrared. In vitro drug release was performed using simulated gastric fluids with 0.1 N HCl (pH 1.2) followed by phosphate buffer (pH 6.5). Results and Discussions: Core tablets give drug release of 98.27-99.59% within 30 min. Hardness of core tablets was in the range of 5-5.2 kg/cm2. Friability values found to be 0.37-0.44%. Drug contents were found for coated tablets in the range of 97.59 Â± 0.24-99.56 Â± 0.23%. The optimized formulation was selected as F2 which gives 99.79% release within 12 h. Conclusion: Pulsatile tablet of Candesartan cilexetil was successfully evaluated, which provided a desired drug release in early morning rise in blood pressure.